Can a Self-Management Education Program for Patients with Chronic Obstructive Pulmonary Disease Improve Quality of Life ? - Manon Labrecque; Khalil Rabhi; Catherine Laurin; Helene Favreau; Gregory Moullec; Kim Lavoie; Marcel Julien (Canadian Respiratory Journal)
OBJECTIVE: To assess the effects of a self-management program on health-related quality of life (HRQoL) and morbidity commonly associated with chronic obstructive pulmonary disease (COPD).